Directional trends in species composition over time can lead to a widespread overemphasis of year‐to‐year asynchrony. (30th July 2020) - Valencia, Enrique; de Bello, Francesco; Lepš, Jan; Galland, Thomas; E‐Vojtkó, Anna; Conti, Luisa; Danihelka, Jiří; Dengler, Jürgen; Eldridge, David J.; Estiarte, Marc; García‐González, Ricardo; Garnier, Eric; et al.
Abstract: Questions: Compensatory dynamics are described as one of the main mechanisms that increase community stability, e.g., where decreases of some species on a year‐to‐year basis are offset by an increase in others. Deviations from perfect synchrony between species (asynchrony) have therefore been advocated as an important mechanism underlying biodiversity effects on stability. However, it is unclear to what extent existing measures of synchrony actually capture the signal of year‐to‐year species fluctuations in the presence of long‐term directional trends in both species abundance and composition (species directional trends hereafter). Such directional trends may lead to a misinterpretation of indices commonly used to reflect year‐to‐year synchrony. Methods: An approach based on three‐term local quadrat variance ( T 3) which assesses population variability in a three‐year moving window, was used to overcome species directional trend effects. This "detrending" approach was applied to common indices of synchrony across a worldwide collection of 77 temporal plant community datasets comprising almost 7, 800 individual plots sampled for at least six years. Plots included were either maintained under constant "control" conditions over time or were subjected to different management or disturbance treatments. Results: Accounting for directional trends increased the detection of year‐to‐year synchronous patterns in all synchrony indices considered. Specifically, synchrony values increased significantly in 40% of the datasets with the T 3 detrending approach while in 10% synchrony decreased. For the 38 studies with both control and manipulated conditions, the increase in synchrony values was stronger for longer time series, particularly following experimental manipulation. Conclusions: Species' long‐term directional trends can affect synchrony and stability measures potentially masking the ecological mechanism causing year‐to‐year fluctuations. As such, previous studies on community stability might have overemphasised the role of compensatory dynamics in real‐world ecosystems, and particularly in manipulative conditions, when not considering the possible overriding effects of long‐term directional trends. Abstract : Measures of community synchrony and stability aim at quantifying year‐to‐year fluctuations in species abundances. However, these indices reflect also long‐term trends, potentially masking year‐to‐year signals. Using a large number of datasets with permanent vegetation plots we show a frequent greater synchrony and stability in year‐to‐year changes compared to when long‐term trends are not taken into account.